2012
DOI: 10.1371/journal.pone.0050062
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Wild-Type ATRX Expression in Somatic Cell Hybrids Segregates with Activation of Alternative Lengthening of Telomeres

Abstract: Alternative Lengthening of Telomeres (ALT) is a non-telomerase mechanism of telomere lengthening that occurs in about 10% of cancers overall and is particularly common in astrocytic brain tumors and specific types of sarcomas. Somatic cell hybridization analyses have previously shown that normal telomerase-negative fibroblasts and telomerase-positive immortalized cell lines contain repressors of ALT activity, indicating that activation of ALT results from loss of one or more unidentified repressors. More recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 45 publications
4
64
0
Order By: Relevance
“…Interestingly, all ALT activated NBLs had these alterations. Therefore, loss of function due to ATRX or DAXX alterations may contribute to ALT activation in NBLs, and it is possible that this is a direct effect of defects of histone H3.3 deposition at telomeres [26,27]. Although ATRX is located in chromosome X, both males and females were found to have ATRX mutations, consistent with previous work [10].…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, all ALT activated NBLs had these alterations. Therefore, loss of function due to ATRX or DAXX alterations may contribute to ALT activation in NBLs, and it is possible that this is a direct effect of defects of histone H3.3 deposition at telomeres [26,27]. Although ATRX is located in chromosome X, both males and females were found to have ATRX mutations, consistent with previous work [10].…”
Section: Discussionsupporting
confidence: 88%
“…As illustrated above, telomerasepositive cultured cells, just like telomerase-positive tumors, exhibited nuclear ATRX, as seen by immunofluorescence, whereas ALT-positive tumors and cultured cells exhibited total loss of nuclear ATRX associated with mutations in ATRX (10,24). This is also illustrated in Fig.…”
Section: Atrx Localizes To Subtelomeric Regions Of Human Glioma Cellssupporting
confidence: 61%
“…Thus, in several clinical studies, mutations in ATRX were found to be tightly associated with the ALT pathway in various types of tumors (10,11,(20)(21)(22)(23). This correlation has also been observed in cultured cells (24,25). To understand how genetic inactivation of ATRX might interfere with telomeric pathways in tumor cells and, in particular, favor the ALT pathway, we used glioma cells in culture because gliomas have been reported to be among the 5 to 15% of tumors that exhibited ALT-maintained telomeres (9).…”
Section: Atrx Localizes To Subtelomeric Regions Of Human Glioma Cellsmentioning
confidence: 66%
“…The same tumors also invariably lacked detectable expression of ATRX and often DAXX [14]. This remarkable correlation between ALT and deregulated ATRX expression was further substantiated by the absence of detectable ATRX protein in 22 ALT cell lines and hybrid cell lines that displayed ALT activity [20,24]. Therefore, ATRX has emerged as the strongest candidate identified to date for the suppression of ALT.…”
Section: Glossarymentioning
confidence: 86%